Secrets for Secondary School Teachers : How to Succeed in Your First Year. - Kottler, Ellen (SAGE Publications, 2003)
In this updated version of the bestseller, you will learn tangible ways to supercharge your teaching skills while avoiding the pitfalls common to beginning teachers.